Experiments of continuously and stably flowing lithium limiter in EAST towards a solution for the power exhaust of future fusion devices. (January 2019) - Hu, J.S.; Zuo, G.Z.; Maingi, R.; Sun, Z.; Tritz, K.; Xu, W.; Yang, Q.X.; Andruczyk, D.; Huang, M.; Meng, X.C.; Gong, X.Z.; Ruzic, D.N.; et al.
Abstract: Liquid lithium (Li) can partly ameliorate lifetime and power-exhaust issues of plasma facing components (PFCs) by enabling a self-healing, self-replenishing surface with a reduced susceptibility to neutron damage in future fusion devices. To assess operational stability and heat-exhaust capability under tokamak exposure, two generations of continuously flowing liquid Li (FLiLi) limiters on the concept of a thin flowing Li film have been successfully designed and tested in high performance discharges in EAST. The design uses a circulating Li layer with a thickness of <0.1 mm and a flow rate ∼2 cm 3 s −1 . In addition, the limiter employs a novel electro-magnetic pump to drive liquid Li flow from a collector at the bottom of the limiter into a distributor at its top. Free surface gravitational flow closes the loop for a continuously flowing liquid Li film on the wetted PFC. Here we summarize key FLiLi limiter development and experimental results in H-mode plasmas.